Learning Media Design for Flat-Sided Space Based on Articulate Storyline for Class VII SMP - Lara Febri Dwi Putri (Akademika, 2024)
Mathematics is a subject with quite abstract material. So, it is not uncommon to be seen as difficult by some students. The low achievement of students in understanding learning materials is because students tend to understand learning Mathematics materials procedurally not conceptually. When learning material is presented in a different form, students have difficulty in understanding the material. With the help of learning media, students have a positive attitude towards learning Mathematics. Learning Mathematics using interactive multimedia needs to be a concern for teachers to improve the learning process in the future. Therefore, the purpose of designing this learning media is to help students in understanding mathematics learning, especially the material of flat-sided space building. In addition, so that this learning media can be used in the learning process. The research was conducted with a descriptive research design. The design of interactive multimedia learning media is followed by media validation, so that the media can be used in the math learning process. There are 3 design activities carried out, namely: designing learning media in mathematics subjects, designing interactive multimedia teaching material content, designing articulate storyline-based interactive multimedia on flat-sided space building material. The design of articulate storyline-based interactive multimedia can increase the involvement of students in the learning process and increase students' understanding of the material of flat-sided spaces. From the results obtained, it can be concluded that the articulate storyline-based interactive multimedia learning media on flat-sided space material that has been designed is feasible to be utilized and developed in mathematics lessons.